Aerospace series. Screw, 100° countersunk normal head, Spiral Drive Recess, close tolerance normal shank, short thread, in titanium alloy, aluminium IVD coated. Classification: 1 100 MPa (at ambient temperature)/425 °C. (8th April 2022) - British Standards Institution
No abstract available